IgD Subtype But Not IgM or Non-Secretory Is a Prognostic Marker for Poor Survival Following Autologous Hematopoietic Cell Transplantation in Multiple Myeloma. Results From the EBMT CALM (Collaboration to Collect Autologous Transplant Outcomes in Lymphomas and Myeloma) Study - Lawless, Sarah; Sbianchi, Giulia; Morris, Curly; Iacobelli, Simona; Bosman, Paul; Blaise, Didier; Reményi, Péter; Byrne, J L; Mayer, Jiri; Apperley, Jane; Lund, Johan; Kobbe, Guido; et al. (Clinical lymphoma, myeloma & leukemia, 2021)
BACKGROUND: The Collaboration to Collect Autologous Transplant Outcomes in Lymphoma and Myeloma (CALM) study has provided an opportunity to evaluate the real-world outcomes of patients with myeloma. The aim of this study was to compare the outcome according to the different subtypes of myeloma using CALM data. PATIENTS: This study compared overall survival (OS), progression-free survival (PFS), and complete remission (CR) and the impact of novel versus non-novel drug containing induction regimens prior to autologous hematopoietic cell transplantation (HCT) of 2802 patients with "usual" and "rare" myelomas. RESULTS: Our data suggest that IgM and non-secretory myeloma have superior PFS and OS compared with IgD myeloma and outcomes comparable to those for usual myeloma. Patients who received novel agent induction had higher rates of CR prior to transplant. Non-novel induction regimens were associated with inferior PFS but no difference in OS. Although not the primary focus of this study, we show that poor mobilization status is associated with reduced PFS and OS, but these differences disappear in multivariate analysis suggesting that poor mobilization status is a surrogate for other indicators of poor prognosis. CONCLUSION: We confirm that IgD myeloma is associated with the worst prognosis and inferior outcomes compared with the other isotypes.
Keywords: senioři; analýza přežití; Immunoglobulin D; Multiple Myeloma; Survival Analysis; doba přežití bez progrese choroby; výsledek terapie; Middle Aged; mužské pohlaví; Adult; mladý dospělý; Transplantation Conditioning; příprava pacienta k transplantaci; Hematopoietic Stem Cell Transplantation; mnohočetný myelom; Young Adult; Transplantation, Autologous; ženské pohlaví; transplantace hematopoetických kmenových buněk; Humans; imunoglobulin D; Progression-Free Survival; lidé středního věku; autologní transplantace; dospělí; Female; Aged; Treatment Outcome; lidé; Male